Dissolved Organic Carbon Turnover in Permafrost-Influenced Watersheds of Interior Alaska: Molecular Insights and the Priming Effect - Textor, Sadie R.; Wickland, Kimberly P.; Podgorski, David C.; Johnston, Sarah Ellen; Spencer, Robert G. M. (Frontiers in Earth Science, 2019)
Increased permafrost thaw due to climate change in northern high-latitudes has prompted concern over impacts on soil and stream biogeochemistry that affect the fate of dissolved organic carbon (DOC). Few studies to-date have examined the link between molecular composition and biolability of dissolved organic matter (DOM) mobilized from different soil horizons despite its importance in understanding carbon turnover in aquatic systems. Additionally, the effect of mixed DOM sources on microbial metabolism (e.g., priming) is not well understood. No studies to-date have addressed potential priming effects in northern high-latitude or permafrost-influenced aquatic ecosystems, yet these ecosystems may be hot spots of priming where biolabile, ancient permafrost DOC mixes with relatively stable, modern stream DOC. To assess biodegradability and priming of DOC in permafrost-influenced streams, we conducted 28 day bioincubation experiments utilizing a suite of stream samples and leachates of fresh vegetation and different soil horizons, including permafrost, from Interior Alaska. The molecular composition of unamended DOM samples at initial and final time points was determined by ultrahigh resolution mass spectrometry. Initial molecular composition was correlated to DOC biodegradability, particularly the contribution of energy-rich aliphatic compounds, and stream microbial communities utilized 50-56% of aliphatics in permafrost-derived DOM within 28 days. Biodegradability of DOC followed a continuum from relatively stable stream DOC to relatively biolabile DOC derived from permafrost, active layer organic soil, and vegetation leachates. Microbial utilization of DOC was ~3-11% for stream bioincubations and ranged from 9% (active layer mineral soil-derived) to 66% (vegetation-derived) for leachate bioincubations. To investigate the presence or absence of a priming effect, bioincubation experiments included treatments amended with 1% relative carbon concentrations of simple, biolabile organic carbon substrates (i.e., primers). The amount of DOC consumed in primed treatments was not significantly different from the control in any of the bioincubation experiments after 28 days, making it apparent that the addition of biolabile permafrost-derived DOC to aquatic ecosystems will likely not enhance the biodegradation of relatively modern, stable DOC sources. Thus, future projections of carbon turnover in northern high-latitude region streams may not have to account for a priming effect.